Pemanfaatan Platform Digital dalam Mendukung Pembelajaran Inovatif di Sekolah Dasar - Syahirah, Dhiyan; Hariandi, Ahmad; Zahyuni, Violita (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The use of digital platforms in elementary schools has become a necessity in supporting innovative learning; however, their implementation has not yet been fully optimized. This study aims to describe the utilization of digital platforms in supporting innovative learning in elementary schools. The study employed a qualitative approach with a case study design involving a classroom teacher and sixth-grade students of SD Negeri 13/I Muara Bulian. Data were collected through observation, interviews, and documentation, and were analyzed using the Miles and Huberman model. The results indicate that Canva and YouTube were utilized in the learning process. Canva was used as the main learning medium accessed through QR codes to present learning materials and practice tasks completed through group discussions, while YouTube was used as a supporting medium to strengthen students’ understanding through instructional videos. However, digital platforms have not been utilized as learning assessment tools, as Quizizz was not implemented. These findings indicate that digital platform-based learning has supported innovative learning, although its implementation has not yet been comprehensive.